FAKTOR YANG BERHUBUNGAN DENGAN TINDAKAN TIDAK AMAN PADA PEKERJA BAGIAN PRODUKSI TIANG PJU PT KUNANGO JANTAN PADANG - Friska Eka Fitria; Dina Waldani Waldani (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
Based on survey was conducted at PT. Kunango Jantan (KJ) obtained work accident data in the production section of PJU poles, 10% of work accident cases. The purpose of this study was to determine the factors associated with unsafe acts on workers in the production section of PJU poles at PT. Kunango Jantan Padang in 2021. This research was conducted at PT. Kunango Jantan in the production of PJU Padang poles in 2021, from February to October. This research is quantitative with cross sectional design, with a population of 65 people. The sampling method in this research is random sampling as many as 39 people. The results of the univariate analysis showed that knowledge of HSE was high (56.4%), training of HSE was not good (53.8%) and supervision of HSE was high (79.5%). The results of the bivariate study showed that there was no relationship between knowledge of HSE with unsafe action (P=0.478), there was no relationship between training of HSE with unsafe action (P=0.823) and there was no relationship between supervision of HSE with unsafe action (p=0.426). It is recommended for further researchers to examine other variables related to unsafe acts such as workload, work stress, work fatigue and it is hoped that the company will further improve the training of workers regarding their work as well as occupational safety and health at PT Kunango Jantan Padang in 2021.Keywords: Knowledge of HSE, training of HSE, supervision of HSE, unsafe action of HSE